Sistem Informasi Administrasi dan Inventory Control pada Multistore UD. XYZ - Gunawan Putra Pratama; Andreas Handojo; Alexander Setiawan (Jurnal Infra, 2020)
UD. XYZ is a trading business in the city of Mataram engaged in the sale of shoes, socks, bags and others. At present UD. XYZ does not have a computerized system for recording. The results of branch sales reports using paper records that will be given by the branch every day to the admin to record requires a long time to make a report. With this problem we need a system that can help record all transactions.To be able to help record all transactions at UD. XYZ is by implementing an administration that can produce reports on sales, purchases, calculating COGS, profit and loss. In addition there is inventory control to help control stock. The system is made using the programming language HTML, PHP, Javascript and MySQL database.The final result of the development of this system is that all branch transactions can be integrated such as purchases, sales, stock. The system can also show a variety of reports such as reports on sales, purchases, profit and loss, debt and others. The system created can also monitor the stock of each branch.